Women’s lived experiences as parking attendants at Wonokromo station, Surabaya - Febriana, Rendra; Ridwan, Ahmad (Jurnal Anifa: Studi Gender dan Anak, 2025)
Women working as parking attendants represent an emerging gender dynamic within the informal employment sector. This study aims to explore the lived experiences of women working as parking attendants through a phenomenological approach. Drawing on Alfred Schutz’s phenomenological theory, particularly the concepts of because-motive and in-order-to motive, this study employs a qualitative research design. Data were collected through in-depth interviews, participant observation, and literature review, while informants were selected using purposive sampling. The primary subject of this study was a female parking attendant working at Wonokromo Station, Surabaya. The findings indicate that women’s involvement in parking attendant work is driven by because-motives such as economic pressures within the household, limited educational background, the availability of informal job opportunities, and situational constraints. Meanwhile, their in-order-to motives reflect aspirations to leave this occupation and seek more secure and socially valued employment. Although this occupation provides a relatively sufficient income, the informants expressed a strong desire to transition to jobs that better align with their personal circumstances, long-term needs, and social expectations. This study contributes to discussions on gender, informal labor, and women’s agency by highlighting how economic necessity intersects with personal aspirations in shaping women’s participation in informal work.